Dakwah Tarekat Syatariyyah Di Nagari Alahan Nan Tigo Provinsi Sumatera Barat - Muharrani Muharrani; Latif Aswen (LPPM STAI Diniyah Pekanbaru, 2019)
This study attempts to uncover dakwah tarekat syatariyyah and the impact of proselytizing conducted by tarekat syatariyyah against the actions of the community in Nagari Alahan Nan Tigo. This research uses descriptive approach qualitative data collection method that is interviews, documentation, and observation. As for a research subject which is an adherent tarekat syatariyyah consisting of teachers and its members. As well as the data analysis technique used is a model interactive analysis, Milles and Huberman, through activities reduction, data the presentation of data, and the withdrawal of conclusion. The research has been done show that tarekat dakwah syatariyyah more individual approach and take a psychological someone like even people who had entered into tarekat then lessons given will be following the state of the person. And in the doctrine of this tarekat be more emphasis on to keep themselves pure and clean of the properties that hasDakwah; Tarekat; Syatariyyahad not good, envy, rumors, And other people hate. Other methods used by tarekat syatariyyah is by using tarekat followers example so that it is easier to understand religion. While the impact or influence of people conducted by tarekat syatariyyah was able to make the alahan nan Tigo as Nagari who run justice and getting along in the shadow of syariatnya prophet Muhammad SAW.